2014
DOI: 10.1161/strokeaha.113.003412
|View full text |Cite
|
Sign up to set email alerts
|

Republished: Society for Neuroscience in Anesthesiology and Critical Care Expert Consensus Statement: Anesthetic Management of Endovascular Treatment for Acute Ischemic Stroke*

Abstract: Abstract-Literature on the anesthetic management of endovascular treatment of acute ischemic stroke (AIS) is limited.Anesthetic management during these procedures is still mostly dependent on individual or institutional preferences. Thus, the Society of Neuroscience in Anesthesiology and Critical Care (SNACC) created a task force to provide expert consensus recommendations on anesthetic management of endovascular treatment of AIS. The task force conducted a systematic literature review (up to August 2012). Bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
146
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(152 citation statements)
references
References 134 publications
1
146
0
5
Order By: Relevance
“…However, data from the literature and a more elaborate interpretation of our results imply that ventilation duration may nevertheless have an impact on clinical outcome. 8,9,21,23 A more thorough insight into our data shows that the missing significance at early and late cutoffs may be partly attributed to the non-normal distribution of our data. In fact, 33 of 42 (78.6%) patients with favorable functional outcome were ventilated for Յ24 hours and only 3 of 42 (7.1%) patients with favorable clinical outcome were ventilated for Ͼ1 week.…”
Section: Ventilation Duration and Clinical Outcomementioning
confidence: 81%
See 2 more Smart Citations
“…However, data from the literature and a more elaborate interpretation of our results imply that ventilation duration may nevertheless have an impact on clinical outcome. 8,9,21,23 A more thorough insight into our data shows that the missing significance at early and late cutoffs may be partly attributed to the non-normal distribution of our data. In fact, 33 of 42 (78.6%) patients with favorable functional outcome were ventilated for Յ24 hours and only 3 of 42 (7.1%) patients with favorable clinical outcome were ventilated for Ͼ1 week.…”
Section: Ventilation Duration and Clinical Outcomementioning
confidence: 81%
“…Hence, our results support the hypothesis that shorter ventilation times are associated with lower pneumonia rates and a more favorable clinical outcome. [21][22][23] When we investigated the influence of ventilation times via various cutoffs, multivariate analyses indicated that longer ventilation times resulted in higher pneumonia rates, regardless of the time of cutoff (Online Table 2). However, multivariate analysis also indicated that longer ventilation times per se had no independent impact on unfavorable functional outcome (P Ն .075).…”
Section: Ventilation Duration and Clinical Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to hemodynamic and time delay issues, there are other compelling reasons why MAC might be preferred over GA. For one, neuro-interventionalists and anesthesiologists would be able to monitor neurological status throughout the procedure, potentially allowing them to more quickly detect complications such as hemorrhage or allowing the procedure to be terminated after neurologic improvement rather than angiographic recanalization. Secondly, MAC avoids hazards associated with intubation and mechanical ventilation, including the placement of a patient on a socalled 'critical care treatment pathway' (22). Finally, MAC typically involves low-dose propofol or other intravenous anesthetic infusions.…”
Section: The Potential Benefits Of Monitored Anesthesia Care: Why?mentioning
confidence: 99%
“…GA remains preferable in patients who cannot protect their airway and MAC is preferable in patients who can protect their airway and are cooperative (class IIa, level B evidence) (22). If GA is chosen for all patients at a given institution based on the preference of the neuro-interventionalists, the patients should be extubated as soon as possible following the procedure.…”
Section: Clinical Implications and Conclusionmentioning
confidence: 99%